Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Jane Fonda signing her book, "Jane Fonda Workout", Lois Lyness in purple; Michael Kanz and Larry Parrot in background